Nobody tosses a Dwarf! – Modelling Gimli being tossed by Aragorn - Roe, Robbie (Journal of Interdisciplinary Science Topics, 2017)
Gimli the Dwarf, a character from The Lord of the Rings, is at one point in the film series tossed by Aragorn into enemies to help buy time for a frantic gate repair at Helm’s Deep. In this paper, the amount of force that Aragorn produces to perform this feat is calculated. By using a number of assumptions and simple physical models, the force with which Gimli was thrown by Aragorn was calculated to be 2767 N, a significant exertion.